Can Amphotericin B-mediated effects be limited using intranasal versus intravenous route? - Siddiqui, Ruqaiyyah; Ong, Timonthy Yu Yee *; Maciver, Sutherland; Khan, Naveed Ahmed (Wiley, 2023)
Aim: CNS infections due to parasites often prove fatal. In part, this is due to inefficacy of drugs to cross the blood-brain barrier. Methods: Here, we tested intranasal and intravenous route and compared adverse effects of Amphotericin B administration, through blood biochemistry, liver, kidney and brain histopathological evidence of toxicities in vivo post-administration. Results: It was observed that intranasal route limits the adverse side effects of Amphotericin B, in contrast to intravenous route. Conclusion: As parasites such as Naegleria fowleri exhibit unequivocal affinity toward the olfactory bulb and frontal lobe in the central nervous system, intranasal administration would directly reach amoebae bypassing the blood-brain barrier selectivity and achieve the minimum inhibitory concentration at the target site.